ANALISIS PENERAPAN SYARIAT ISLAM DALAM SEKTOR PERBANKAN PASCA PELAKSANAAN SYARIAT ISLAM DI ACEH, INDONESIA: Analysis of Islamic Shariah Application in the Banking Sector Post-Islamic Shariah Implementations in Aceh, Indonesia - Jailani, Munawar Rizki; Mohamad, Mohammad Taqiuddin (Jurnal Syariah, 2019)
The application of Shariah in general on the aspect of life is the specialty of Aceh which is entrusted by the Law of the Unitary State of the Republic of Indonesia. This study focuses on the analysis of the implementation of Shariah in the banking sector following the implementation of Islamic Shariah in Aceh. The method applied in this study uses a qualitative approach by referring to the study of the case of Shariah application in the banking sector in Aceh, whereas the research data is derived from library research, documentation and interviews with related parties in the implementation of Shariah in banking in Aceh. Then the data is processed using the content analysis method whether inductive, deductive or comparative. The findings show that the implementation of Shariah in the banking sector in Aceh has not been in line with the implementation of the overall application, there are still conventional banks that operate in Aceh. Also, the Shariah application in the banking sector is still less than those in areas who are impressed with the attention of the Aceh government. The Application of Islamic Shariah in the banking sector is still in the stage of an idea to run yet to the stage of implementation.